The effect of informational prompts about survivor benefits for spouses on Social Security claim intentions. (13th October 2021) - Perez-Arce, Francisco; Rabinovich, Lila; Samek, Anya; Yoong, Joanne
Abstract: Married men's Social Security claiming behavior does not always take into account spouse and survivor benefits. Specifically, married men tend to choose claiming ages that do not maximize the household's and widow's expected present value of benefits. To understand what contributes to this pattern, we conduct an online survey experiment with a representative sample of Americans. We randomly assign respondents to one of four vignettes that present information about a character who is choosing when to claim his retirement benefits. The vignettes differ by whether the character is married or not, whether information about survivor benefits is presented, and whether the information includes an illustrative example. We next ask respondents to provide advice to the character about when to claim. We find that (1) respondents do value survivor benefits for spouses, and (2) information about survivor benefits tends to increase the suggested claiming ages only among the subgroup of respondents who are the least knowledgeable about these benefits.